Effectiveness Test of Mixed Extract of Tanjang merah (Bruguiera gymnorrhiza) and Bogem (Sonneratia caseolaris) in Preserved Milkfish (Chanos chanos) - Aminah, Siti; Ramadhan, Majida; Latuconsina, Husain (Agrikan Jurnal Agribisnis Perikanan, 2023)
The aims of this study were: 1. To test the effectiveness of a mixture of Bruguiera gymnorrhiza leaf extract and Sonneratia caseolaris leaf as an inhibitor of bacterial growth, 2. To test the concentration of the most effective extract as a natural preservative for ibandeng fish (Chanos chanos) as an inhibitor of bacterial growth and 3. Testing the storage time of milkfish using a mixed extract of Bruguiera gymnorrhiza leaves and Sonneratia caseolaris leaves at room temperature 4. Organoleptic test assessment of the quality of milkfish. This study used an experimental method with 3 treatments, namely the addition of a mixture of leaf extracts of Bruguiera gymnorrhiza and leaves of Sonneratia caseolaris in a ratio of 1:1, 1:2 and 2:1, with storage time at room temperature of 6 hours, 12 hours and 18 hours and organoleptic tests. . The results of this study showed that the mixed extract of Bruguiera gymnorrhiza and Sonneratia caseolaris leaves was effective as an inhibitor of bacterial growth. The lowest value of bacterial colonies was at a concentration of 2:1 with a storage time of 6 hours. Organoleptic test showed that the use of leaves of Bruguiera gymnorrhiza and leaves of Sonneratia caseolaris can have an effect on milkfish in the eyes, gills and mucus. Based on the results of the study, it can be concluded that the mixed extract of Bruguiera gymnorrhiza leaves and Sonneratia caseolaris leaves has the ability as a natural preservative in milkfish.